PENGEMBANGAN MEDIA KOMIK DIGITAL BERBASIS CANVA PADA MUATAN PELAJARAN BAHASA INDONESIA MATERI SUMBER ENERGI - Sucita Nurafrilian; Elly Sukamanasa; Yudhie Suchyadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to develop an innovation in interesting, varied, and innovative learning media using the Canva application as well as to test the feasibility and validity of the developed media, namely Canva-based digital comic media in Indonesian language lesson content on energy source materials. This type of research is a research and development research with the research subjects of class III students at SDN Kawungluwuk Kab. Cianjur. Data collection in this study used the methods of observation, interviews, and documentation. Data were analyzed using quantitative and qualitative descriptive analysis. The procedure and stages of development on Canva-based digital comic media use the ADDIE model which has five stages, namely analysis, design, development, implementation, and evaluation. The quantitative and qualitative development of digital comics based on Canva is appropriate for use in learning. The results of the validation assessment were processed twice because of revisions to produce the best product. The results of the 1st media expert validator got 91% and the 2nd got 92%, the 1st linguist validator got 64% and the 2nd got 100%, the 1st material expert validator got 84% and the 2nd got 88%. The overall results of all validators 1 get 80% results and the 2nd get 93% results have an increase. Meanwhile, the results of the student response questionnaire obtained 94%. Based on the results of the study, it was shown that the Canva-based digital comic media in the Indonesian language subject matter of energy source material was very feasible to be used as a varied and innovative learning media in learning. Keywords: Development; Learning media innovation; Digital Comics; Canva; Energy sources